Perancangan Aplikasi E-Learning Berbasis Web dengan Model Prototype pada SMPN 7 Kota Tangerang Selatan - Robbi, Mukhlishoh Syaukati; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Learning is the process of student interaction with educators and learning resources in a learning environment that includes teachers and students who exchange information. Therefore, learning must go well so that information can be delivered. Educators who are unable to attend will disrupt the delivery of learning material. Likewise, for students who are unable to attend will certainly miss the learning material provided by educators. With E-Learning making it easy in the process of teaching and learning activities in schools, teachers can provide materials and assignments anywhere, students are easy to get learning materials, and make it easy for students to do the assignments given by the teacher, without being hindered by the dimensions of space and time. The system development method used by the authors in conducting this research is the Prototype method. The Prototype method is prototyping software or life cycle using prototyping. One method of system life cycle is based on the concept of a working model. Where the system developer and client can see and conduct experiments since the beginning of the development process. In the Prototype method there are three stages (3) development cycle, namely: Requirement Collection Phase, Prototype Building Phase, and Trial Phase.